Child care in action preschool - Hoffman, Sara McCormack ([s.l.] : Thomson Delmar Learning, 2005)
Provides information specific to preschool child care , development and program management
System requirement : Windows Pentium computer ; Windows 98/2000/XP/2003 ; CD-ROM drive , Acrobat Reader ; Macromedia Flash Player
Keywords: Child care; Child development; Child rearing; Preschool children